REKONSTRUKSI IDENTITAS BUDAYA WARGA MUSLIM AMERIKA PASCASERANGAN SEBELAS SEPTEMBER 2001 (RECONSTRUCTION OF CULTURAL IDENTITY OF AMERICAN MUSLIMS IN THE AFTERMATH OF SEPTEMBER 11TH ATTACKS) - , M. Thoyibi, Drs.,MS.; , Prof Dra. Djuhertati Imam Muhni, M.A., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study deals with the dynamics of American Muslims in coping with the identity conflicts in the aftermath of September Eleventh Attacks. This study aims at describing the reconstruction of cultural identity of American Muslims and revealing the underlying reasons of the reconstruction. The study used the qualitative method. The types of the data were words or statements, either written or spoken, and events or actions conducted by the subjects of the study. The data sources consisted of printed documents, audio/visual records, statistics, images/photos, literary works, and films. The methods of collecting the data were library research, internet browsing, observation, and interview by email. The analyzing techniques were descriptive-analytic technique, categorization, and interpretation. The study found that in the aftermath of the September Eleventh Attacks, American Muslims underwent some changes, particularly in the mental and social dimensions. The changes in the mental dimension were reflected in the different way of identifying the citizenship, identity configuration, and the position of American Islam. The changes in the social dimension could be identified from the response to religious extremism, behavior towards other religious groups, and representation of Muslim women. They also produced some publications, such as statement, advertisement, fatwa, posters, video, and reality show in addition to the interfaith institutions. The findings implied that American Muslims underwent a cultural identity reconstruction constituting a survival strategy of the minority group against the threat of the dominant culture. They reconstructed their identity by seeking for the meeting points between Islam and American culture and by keeping the religious principle.